El enfoque sistémico en la intervención psicopedagógica para desarrollar habilidades de autorregulación Emocional en estudiantes de octavo año de educación general básica de la unidad educativa réplica Nicolás Infante Díaz. - Mendoza Ibarra , María Fernanda (2025)
The research focuses on the design of a psychopedagogical intervention program with a systemic approach for eighth-grade students in General Basic Education at the “Réplica Nicolás Infante Díaz” Educational Unit, with the aim of promoting the development of emotional self-regulation skills. Starting from the perspective of the systemic approach, which highlights the interdependence between family and school, the factors that limit the absence of emotional management skills were analyzed, such as low tolerance for frustration, impulsive responses, aggressive attitudes, and difficulties in resolving conflicts peacefully. Using a qualitative methodology based on the triangulation of instruments, observation sheets were completed, interviews were conducted with legal representatives and teachers, and a focus group was held with selected students to identify psycho-pedagogical needs, analyze the influence of family and school factors on the development of emotional self-regulation skills, and design appropriate activities within the intervention program. A program was structured consisting of key activities for emotional strengthening, including awareness, regulation, autonomy, social skills, and life skills to improve coexistence at home and school. It is hoped that in future applications, this psycho-pedagogical intervention program will contribute to the development of skills.